2000
DOI: 10.1017/s0021963099006186
|View full text |Cite
|
Sign up to set email alerts
|

On the “Specifics” of Specific Reading Disability and Specific Language Impairment

Abstract: The reading and oral language scores of 110 children with a specific reading disability (SRD) and 102 children with a specific language impairment (SLI) indicated that approximately 53 % of children with an SRD and children with an SLI could be equally classified as having an SRD or an SLI, 55 % of children with an SRD have impaired oral language, and 51 % of children with an SLI have a reading disability. Finding that a large percentage of children can be equally classified as SRD or SLI has repercussions for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
224
1
23

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(269 citation statements)
references
References 21 publications
21
224
1
23
Order By: Relevance
“…Recent research suggests that SLI and developmental dyslexia can best be treated as distinct, yet closely associated and potentially comorbid, language disorders (see Bishop & Snowling, 2004;Catts, Adlof, Hogan, & Ellis Weismer, 2005). On the one hand, oral language deficits are commonly reported in children with dyslexia (e.g., McArthur et al, 2000;Starck & Tallal, 1988). On the other hand, high rates of literacy problems are reported in children with SLI (e.g., Conti-Ramsden, Botting, Simkin, & Knox, 2001;Haynes & Naidoo, 1991;Tallal, Allard, Miller, & Curtiss, 1997), consistent with the link between lexicality and literacy explained above.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research suggests that SLI and developmental dyslexia can best be treated as distinct, yet closely associated and potentially comorbid, language disorders (see Bishop & Snowling, 2004;Catts, Adlof, Hogan, & Ellis Weismer, 2005). On the one hand, oral language deficits are commonly reported in children with dyslexia (e.g., McArthur et al, 2000;Starck & Tallal, 1988). On the other hand, high rates of literacy problems are reported in children with SLI (e.g., Conti-Ramsden, Botting, Simkin, & Knox, 2001;Haynes & Naidoo, 1991;Tallal, Allard, Miller, & Curtiss, 1997), consistent with the link between lexicality and literacy explained above.…”
Section: Discussionmentioning
confidence: 99%
“…Both groups have been found to show deficits in speech perception, phonological awareness, repeating words and sentences, grammaticality judgment and rapid naming. The phenotypical similarity between dyslexia and SLI is demonstrated by MacArthur et al (2000), in which a blind re-evaluation procedure revealed that about 50% of both dyslexic children and children with SLI fulfilled the criteria of the alternative diagnostic category.…”
Section: Introductionmentioning
confidence: 99%
“…Dyslexic individuals vary in types of reading errors, presence of other developmental disorders (e.g. language delay [2]) and the extent of perceptual difficulties [3]. Perceptual deficits in dyslexia have been found on both visual [4] and auditory [5][6][7] tasks.…”
Section: Introductionmentioning
confidence: 99%